Eloquent Lower Grade Gliomas, a Highly Vulnerable Cohort: Assessment of Patients’ Functional Outcome After Surgery Based on the LoG-Glio Registry - Coburger, Jan; Onken, Julia; Rueckriegel, Stefan; von der Brelie, Christian; Nadji-Ohl, Minou; Forster, Marie-Therese; Gerlach, Rüdiger; Unteroberdörster, Meike; Roder, Constantin; Kniese, Katja; Schommer, Stefan; Rothenbacher, Dietrich; et al. (Frontiers in Oncology, 2022)
Majority of lower grade glioma (LGG) are located eloquently rendering surgical resection challenging. Aim of our study was to assess rate of permanent deficits and its predisposing risk factors. We retrieved 83 patients harboring an eloquently located LGGs from the prospective LoG-Glio Database. Patients without surgery or incomplete postoperative data were excluded. Sign rank test, explorative correlations by Spearman ρ and multivariable regression for new postoperative deficits were calculated. Eloquent region involved predominantly motor (45%) and language (40%). At first follow up after 3 months permanent neuro-logical deficits (NDs) were noted in 39%. Mild deficits remained in 29% and severe deficits in 10%. Complete tumor removal (CTR) was successfully in 62% of intended cases. Postoperative and 3-month follow up National Institute of Health Stroke Score (NIHSS) showed significantly lower values than preoperatively (p<0.001). 38% cases showed a decreased NIHSS at 3-month, while occurrence was only 14% at 9-12-month follow up. 6/7 patients with mild aphasia recovered after 9-12 months, while motor deficits present at 3-month follow up were persistent in majority of patients. Eastern oncology group functional status (ECOG) significantly decreased by surgery (p < 0.001) in 31% of cases. Between 3-month and 9-12-months follow up no significant improvement was seen. In the multivariable model CTR (p=0.019, OR 31.9), and ECOG>0 (p=0.021, OR 8.5) were independent predictors for permanent postoperative deficit according to NIHSS at 3-month according to multivariable regression model. Patients harboring eloquently located LGG are highly vulnerable for permanent deficits. Almost one third of patients have a permanent reduction of their functional status based on ECOG. Risk of an extended resection has to be balanced with the respective oncological benefit. Especially, patients with impaired pre-operative status are at risk for new permanent deficits. There is a relevant improvement of neurological symptoms in the first year after surgery, especially for patients with slight aphasia.